Clinical features of Chinese children with COVID‐19 and other viral respiratory infections - Zhang, Zhen‐Zhen; Chen, Da‐Peng; Liu, Quan‐Bo; Gan, Chuan; Jiang, Li; Zhu, Kun; Zhang, Xia‐Yi; Xu, Hong‐Mei; Huang, Ai‐Long; Long, Quan‐Xin; Deng, Hai‐Jun; Chen, Juan (Pediatric pulmonology, 2022)
Objective Few studies have explored the clinical features in children infected with SARS‐CoV‐2 and other common respiratory viruses, including respiratory syncytial virus (RSV), Influenza virus (IV), and adenovirus (ADV). Herein, we reported the clinical characteristics and cytokine profiling in children with COVID‐19 or other acute respiratory tract infections (ARTI). Methods We enrolled 20 hospitalized children confirmed as COVID‐19 positive, 58 patients with ARTI, and 20 age and sex‐matched healthy children. The clinical information and blood test results were collected. A total of 27 cytokines and chemokines were measured and analyzed. Results The median age in the COVID‐19 positive group was 14.5 years, which was higher than that of the ARTI groups. Around one‐third of patients in the COVID‐19 group experienced moderate fever, with a peak temperature of 38.27°C. None of the patients displayed wheezing or dyspnea. In addition, patients in the COVID‐19 group had lower white blood cells, platelet counts as well as a neutrophil‐lymphocyte ratio. Lower serum concentrations of 14 out of 27 cytokines were observed in the COVID‐19 group than in healthy individuals. Seven cytokines (IL‐1Ra, IL‐1β, IL‐9, IL‐10, TNF‐α, MIP‐1α, and VEGF) changed serum concentration in COVID‐19 compared with other ARTI groups. Conclusion Patients with COVID‐19 were older and showed milder symptoms and a favorable prognosis than ARTI caused by RSV, IV, and ADV. There was a low grade or constrained innate immune reaction in children with mild COVID‐19.